TO ASSESS THE LEVEL OF SATISFACTION OF BUYERS IN THE REAL ESTATE SECTOR - Mohindru, Pankaj; Kaur, Jasmeen (International Journal of Research -GRANTHAALAYAH, 2023)
The interpretation of customer satisfaction is a complex task due to its subjective nature, which is contingent upon the individual preferences and experiences of each customer. The Real Estate industry presents a heightened level of complexity as there exist numerous factors that contribute to the determination of customer satisfaction. Customer satisfaction is closely linked to the perception of the customer, whereby meeting the customer’s perceived expectations results in their satisfaction. This research is on the Indian real estate business. This study was primarily conducted to assess the level of satisfaction of buyers in the real estate sector. The principal goal of this study was to examine the satisfaction level of buyers while buying a residential property. The paper is helpful for real estate agents. It helps real estate agents understand what buyers want and how they think.